The effect of Favipiravir on liver enzyme among patients with mild to moderate COVID-19 infection: A prospective cohort study - Al-Shammari, Ahmed Hamza; Mohammed Abd Ali Shahadha (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Teratogenicity and hyperuricemia are considered as the major adverse effects of favipiravir, but less is known about other possible side effects which includes drug-induced liver damage and renal injury. In the current research, assessment of favipiravir-induced liver injury was performed by evaluating liver enzymes among patients with mild to moderate COVID-19 infection.A prospective cohort study was conducted on 66 patients diagnosed with mild to moderate COVID-19 infection who were treated with favipiravir for 5 days. During this period, a baseline assessment of liver enzymes (aspartate aminotransferase – AST, ala-nine transaminase – ALT and alkaline phosphatase – ALP) in addition to bilirubin before initiation of ther-apy and after 1 day of completion of therapy were carried out. The comparison of all measured parameters among all patients before and after receiving the treatment showed that non-significant differences were obtained in their levels. It was noticed that COVID-19 patients demonstrated high AST levels in which only 16 patients out of the all-subjected cases (66 patients) had AST levels of less than 45 U/L whereas the major-ity of patients showed normal ALT, ALP, and bilirubin levels. It was concluded that 5 days administration of favipiravir in mild to moderate COVID-19 patients who had no previous liver diseases did not affect the liver enzymes significantly and only transient elevations were occurred.